Differences in gait analysis and clinical outcome after dynamic fixation or screw fixation in acute syndesmosis tear: a prospective randomized pilot study - Mick, Paul; Doll, Julian; Müller, Michelle; Schmidmaier, Gerhard; Renkawitz, Tobias; Campos, Sarah; Wolf, Sebastian Immanuel; Tsitlakidis, Stefanos (Archives of orthopaedic and trauma surgery, 2024)
Acute syndesmosis tears can be treated by static screw or dynamic fixation. Various studies have compared these techniques regarding postoperative outcome. However, to our knowledge, no study has used 3D-instrumented gait analysis (IGA). We hypothesized that a dynamic fixation would perform non-inferior to screw fixation in terms of biomechanical and clinical outcomes.
Gesehen am 01.04.2025
Veröffentlicht: 11. September 2024